(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1913)
It is traditionally held that Edinburgh Castle was captured from the English in the year before the battle of Bannockburn but it is unclear whether the attack came from the northern or the southern side. Sir Walter Scott believed the ascent was made on the southern side. The author favours the northern side.